HUBUNGAN ANTARA OPTIMISME DAN SELF EFFICACY DENGAN RESILIENSI WARGA DUSUN JAMBEREJO DAN KRAJANSAE DI MASA PANDEMI COVID 19 DESA BEJI KECAMATAN JUNREJO KOTA BATU - Rr. Hesti Setyodyah Lestari; Wafiyatu Maslahah; Achmad Wahyudi (Media Bina Ilmiah, 2022)
This study has the aim of knowing whether or not there is a relationship between optimisme and self-efficacy with resilience of the residents of the jamberejo hamlet and Krjansae during the COVID-19 pandemic with a sample of 201 residents living in the Beji vilage, Junrejo sub district in the city of Batu, the respondents. At the same time, there is a relationship between Optimisme and self-efficacy with family resilience in residents of the the Beji vilage, Junrejo sub district in the city of Batu, with a significant value equal to p = 0,001 (p < 0,001). The lower the level of optimisme and self-efficacy experienced by residents in the the Beji vilage, Junrejo sub district in the city of Batu, the lower the family resilience experienced by residents in the the Beji vilage, Junrejo sub district in the city of Batu. The expectation variable Optimisme has a significance value of t = -2.672 > 0,001 , that is, there is a significant effect of the Optimisme variable on the resilience variable. The expected variable Self efficacy has a significance value of t = 13.199 < 0,001 , that is, there is a significant effect of the self-efficacy variable on the family resilience variable.